Effective Mechanical Properties of Nanocomposites Reinforced With Carbon Nanotubes Bundle - M. Hashemi Gahruei (Journal of Sciences, Islamic Republic of Iran)
Nanocomposites made of Carbon Nanotube (CNT) bundles have attracted researchers’ attention due to their unusual properties such as: light weight, flexibility and stiffness.  In this paper, the effects of straight and rope-shaped bundles on nanocomposite effective mechanical properties are investigated.  First, FEA models are created consisting of CNTs with different shapes of straight and rope-shaped bundles to investigate the effects of straight and rope-shaped bundles dimensions.  Next, the reinforcing efficiency of CNTs in different matrices is investigated using models consisting of matrices with different moduli of elasticity.  The results show that the increases of Young’s modulus of matrix and straight bundle and rope-shaped bundle diameter can significantly reduce the stiffening effect of the nanotubes in longitudinal fiber and increase the stiffening effect of the nanotubes in transverse fiber.  Also, Young’s modulus prediction for carbon nanotube in a poly (ethylene terephthalate) matrix is compared to experimental data investigated by Gómez-del Río et al. (2010), and good agreement is observed.